Reimagining Science Education in the Anthropocene - Wallace, Maria F. G.; Bazzul, Jesse; Higgins, Marc; Tolbert, Sara (Palgrave Studies in Education and the Environment, 2022)
This open access edited volume invites transdisciplinary scholars to re-vision science education in the era of the Anthropocene. The collection assembles the works of educators from many walks of life and areas of practice together to help reorient science education toward the problems and peculiarities associated with the geologic times many call the Anthropocene. It has become evident that science education-the way it is currently institutionalized in various forms of school science, government policy, classroom practice, educational research, and public/private research laboratories-is ill-equipped and ill-conceived to deal with the expansive and urgent contexts of the Anthropocene. Paying homage to myopic knowledge systems, rigid state education directives, and academic-professional communities intent on reproducing the same practices, knowledges, and relationships that have endangered our shared world and shared presents/presence is misdirected. This volume brings together diverse scholars to reimagine the field in times of precarity.